Mononuclear Copper(I) 3-(2-pyridyl)pyrazole Complexes: The Crucial Role of Phosphine on Photoluminescence - Kristina F. Baranova (MDPI AG, 2021)
A series of emissive Cu(I) cationic complexes with 3-(2-pyridyl)-5-phenyl-pyrazole and various phosphines: dppbz (1), Xantphos (2), DPEPhos (3), PPh3 (4), and BINAP (5) were designed and characterized. Complexes obtained exhibit bright yellow-green emission (ca. 520–650 nm) in the solid state with a wide range of QYs (1–78%) and lifetimes (19–119 µs) at 298 K. The photoluminescence efficiency dramatically depends on the phosphine ligand type. The theoretical calculations of buried volumes and excited states explained the emission behavior for 1–5 as well as their lifetimes. The bulky and rigid phosphines promote emission efficiency through the stabilization of singlet and triplet excited states.